Myxococcus xanthus R31 Suppresses Tomato Bacterial Wilt by Inhibiting the Pathogen Ralstonia solanacearum With Secreted Proteins - Dong, Honghong; Xu, Xin; Gao, Ruixiang; Li, Yueqiu; Li, Anzhang; Yao, Qing; Zhu, Honghui (Frontiers in Microbiology, 2022)
The pathogenic bacterium Ralstonia solanacearum caused tomato bacterial wilt (TBW), a destructive soil-borne disease worldwide. There is an urgent need to develop effective control methods. Myxobacteria are microbial predators and are widely distributed in the soil. Compared with other biocontrol bacteria that produce antibacterial substances, the myxobacteria have great potential for biocontrol. This study reports a strain of Myxococcus xanthus R31 that exhibits high antagonistic activity to R. solanacearum. Plate test indicated that the strain R31 efficiently predated R. solanacearum. Pot experiments showed that the biocontrol efficacy of strain R31 against TBW was 81.9%. Further study found that the secreted protein precipitated by ammonium sulfate had significant lytic activity against R. solanacearum cells, whereas the ethyl acetate extract of strain R31 had no inhibitory activity against R. solanacearum. Substrate spectroscopy assay and liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis of secreted proteins showed that some peptidases, lipases, and glycoside hydrolases might play important roles and could be potential biocontrol factors involved in predation. The present study reveals for the first time that the use of strain M. xanthus R31 as a potential biocontrol agent could efficiently control TBW by predation and secreting extracellular lyase proteins.